Pharmacophore-based screening of differentially-expressed PGF, DDIT4, COMP and CHI3L1 from hMSC cell lines reveals five novel therapeutic compounds for primary osteoporosis - Catherine Jessica Lai (Journal of Genetic Engineering and Biotechnology, 2016)
As many societies age, primary osteoporosis (PO) is increasingly a major health problem. Current drug treatments such as alendronate and risedronate have known side effects. We took an agnostic empirical approach to find PO therapeutic compounds. We examined 13,548,960 probe data-points from mesenchymal stromal cell (hMSC) lines and found that PGF, DDIT4, and COMP to be up-regulated, and CHI3L1, down-regulated. We then identified their druggable domains. For the up-regulated differentially-expressed genes, we used protein–protein interactions to find residue clusters as binding surfaces. We then employed pharmacophore models to screen 15,407,096 conformations of 22,723,923 compounds, which identified (6R,9R)-6-(2-furyl)-9-(1H-indol-3-yl)-2-(trifluoromethyl)-5,6,7, 9-tetrahydro-4H[1,2,4]triazolo[5,1],(2S)-N1-[2-[2-(methylamino)-2-oxo-ethyl]phenyl]-N2-phenylpyrrolidine-1,2-dicarboxamide, and 2-furyl-(1H-indol-3-yl)-methyl-BLAHone as candidate compounds. For the down-regulated CH13L1, we relied on genome-wide disease signatures to identify (11alpha)-9-fluoro-11,17,21-trihydroxypregn-4-ene-3,20-dione and Genistein as candidate compounds. Our approach differs from previous research as we did not confine our drug targets to hypothesized compounds in the existing literature. Instead, we allowed the full expression profile of PO cell lines to reveal the most desirable targets. Second, our differential gene analysis revealed both up- and down-regulated genes, in contrast to the literature, which has focused on inhibiting only up-regulated genes. Third, our virtual screening universe of 22,723,923 compounds was more than 100 times larger than those in the known literature.